2016
DOI: 10.1128/mbio.01691-16
|View full text |Cite
|
Sign up to set email alerts
|

The PAS Domain-Containing Protein HeuR Regulates Heme Uptake in Campylobacter jejuni

Abstract: Campylobacter jejuni is a leading cause of bacterially derived gastroenteritis. A previous mutant screen demonstrated that the heme uptake system (Chu) is required for full colonization of the chicken gastrointestinal tract. Subsequent work identified a PAS domain-containing regulator, termed HeuR, as being required for chicken colonization. Here we confirm that both the heme uptake system and HeuR are required for full chicken gastrointestinal tract colonization, with the heuR mutant being particularly affect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…1d ). chuA is not required for chicken colonization 26 and is modestly upregulated in the chick cecum (<10 fold increase in vivo ), although it is highly upregulated in human infection samples (>1000 fold increase in vivo ). There are 161 genes that are differentially regulated specifically in our human samples and not in the chick cecum ( Fig.…”
Section: Campylobacter Gene Expression In Human Infection Samplesmentioning
confidence: 98%
“…1d ). chuA is not required for chicken colonization 26 and is modestly upregulated in the chick cecum (<10 fold increase in vivo ), although it is highly upregulated in human infection samples (>1000 fold increase in vivo ). There are 161 genes that are differentially regulated specifically in our human samples and not in the chick cecum ( Fig.…”
Section: Campylobacter Gene Expression In Human Infection Samplesmentioning
confidence: 98%
“…In addition to Fur regulation, other regulatory proteins have been found that bind to the same promoters as Fur, indicating co-regulation of some cellular systems. In C. jejuni , a PAS-domain containing regulatory protein, termed HeuR, was found to positively regulate the heme utilization system and also bind to a promoter fragment that contains putative Fur binding sites (Ridley et al, 2006; Johnson et al, 2016). This regulator which is specific to the Campylobacter genus, did not impact transcription of Fur, indicating that it may work with Fur to control heme utilization in C. jejuni .…”
Section: Introductionmentioning
confidence: 99%
“…These data sets suggest Cj RidA could play a direct or indirect role in virulence, antibiotic resistance, acid adaptation, growth with bile salts, and hydrogen peroxide and oxygen stress. Finally, cj ridA is a member of the HeuR ( He me u tilization r egulator) regulon (Reuter et al, 2015; Johnson et al, 2016). HeuR is a PAS-domain containing regulator, and thought to be regulated in response to changing environmental cues (Reuter et al, 2015; Johnson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%